Identificação de Parâmetros de uma Junta de um Manipulador Baseado em Mínimos Quadrados para Controle de Ganho Constante - Silva, Francisco Heleno Vitor da (2023)
This work presents the identification through the mathematical method of non-recursive MQ, of the model of a rotational joint of a cylindrical manipulator driven by MIT and the application of PID and PID 2-DOF controllers. From the 2nd order model found by MQ of the robotic manipulator joint, the 1st order model is identified using the step reaction curve method to calculate the parameters K, τ and θ of the tuning methods proposed to control the speed. The tuning methods ZN, CHR, IMC and SIMC were used. To compare the results of the controllers, the following performance criteria are used: rise time (tr), settling time (ts), overshoot, IAE and ISE. Simulations were carried out with positive and negative step input profiles and sinusoidal input to evaluate the performance of the PID and PID 2-DOF controllers for each proposed tuning method. In the simulations, the PID controller showed better performance for the proposed tuning methods in relation to those presented by PID 2-DOF, with emphasis on the ZN tuning method that obtained the best tr , the CHR method with the best ts and the IMC method that did not present overshoot. Finally, the PID controller was implemented on an experimental bench with the ZN and IMC tuning methods, obtaining satisfactory results in both cases, with the highlight of better tr and ts of the IMC method.